Early formative objective structured clinical examinations for students in the pre-clinical years of medical education: A non-randomized controlled prospective pilot study. - Naïm Ouldali; Enora Le Roux; Albert Faye; Claire Leblanc; François Angoulvant; Diane Korb; Clémence Delcour; Caroline Caula; Delphine Wohrer; Alexis Rybak; Manon Delafoy; Claire Carrié; et al. (PLoS ONE)
Background The value of formative objective structured clinical examinations (OSCEs) during the pre-clinical years of medical education remains unclear. We aimed to assess the effectiveness of a formative OSCE program for medical students in their pre-clinical years on subsequent performance in summative OSCE. Methods We conducted a non-randomized controlled prospective pilot study that included all medical students from the last year of the pre-clinical cycle of the Université Paris-Cité Medical School, France, in 2021. The intervention group received the formative OSCE program, which consisted of four OSCE sessions, followed by debriefing and feedback, whereas the control group received the standard teaching program. The main objective of this formative OSCE program was to develop skills in taking a structured medical history and communication. All participants took a final summative OSCE. The primary endpoint was the summative OSCE mark in each group. A questionnaire was also administered to the intervention-group students to collect their feedback. A qualitative analysis, using a convenience sample, was conducted by gathering data pertaining to the process through on-site participative observation of the formative OSCE program. Results Twenty students were included in the intervention group; 776 in the control group. We observed a significant improvement with each successive formative OSCE session in communication skills and in taking a structured medical history (p<0.0001 for both skills). Students from the intervention group performed better in a summative OSCE that assessed the structuring of a medical history (median mark 16/20, IQR [15; 17] versus 14/20, [13; 16], respectively, p = 0.012). Adjusted analyses gave similar results. The students from the intervention group reported a feeling of improved competence and a reduced level of stress at the time of the evaluation, supported by the qualitative data showing the benefits of the formative sessions. Conclusion Our findings suggest that an early formative OSCE program is suitable for the pre-clinical years of medical education and is associated with improved student performance in domains targeted by the program.